MicroRNA-200c affects bladder cancer angiogenesis by regulating the Akt2/mTOR/HIF-1 axis - Wu, Shui-Qing; He, Hai-Qing; Kang, Ye; Xu, Ran; Zhang, Lei; Zhao, Xiao-Kun; Zhu, Xuan (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: Bladder cancer is one of the most frequent urologic tumours in the world. MicroRNA- 200c (miR-200c) has been considered a regulator of tumour angiogenesis. Akt2/mTOR was considered a regulator of vascular endothelial growth factor (VEGF) and hypoxia-inducible factor 1α (HIF-1α). However, the mechanism by which miR-200c regulates bladder cancer angiogenesis remains unknown. Methods: Western blotting and qRT-PCR were used to detect the expression of protein and mRNA, respectively. Cell proliferation, migration and invasion were detected using MTT, wound-healing and transwell assays, respectively. A dual luciferase reporter assay was used to identify the binding site between miR-200c and Akt2. A tube formation assay was also applied to detect the angiogenesis ability. Results: Significantly higher expression levels of HIF-1α and VEGF and lower levels of miR-200c were observed in three types of bladder cancer cell lines. Transfection with the miR-200c mimic markedly inhibited cell viability, angiogenesis, and the expression of VEGF and HIF-1α. Overexpression of miR-200c remarkably suppressed the expression of Akt2, and the binding site between them was identified. Knockdown of Akt2 remarkably decreased the expression of VEGF and HIF-1α by regulating mTOR. miR-200c influenced the expression of VEGF and HIF-1α through the Akt2/mTOR signalling pathway and further regulated angiogenesis in bladder cancer cells. Conclusions: We proved that miR-200c could suppress HIF-1α/VEGF expression in bladder cancer cells and inhibit angiogenesis, and these regulations were achieved by targeting Akt2/mTOR. This study may provide new insight into the prevention and treatment of bladder cancer.